2018
DOI: 10.1113/jp275222
|View full text |Cite
|
Sign up to set email alerts
|

Genioglossus reflex responses to negative upper airway pressure are altered in people with tetraplegia and obstructive sleep apnoea

Abstract: More than 60% of people with tetraplegia have obstructive sleep apnoea (OSA). However, the specific causes are unknown. Genioglossus, the largest upper-airway dilator muscle, is important in maintaining upper-airway patency. Impaired genioglossus muscle function following spinal cord injury may contribute to OSA. This study aimed to determine if genioglossus reflex responses to negative upper-airway pressure are altered in people with OSA and tetraplegia compared to non-neurologically impaired able-bodied indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…The delayed reflex latency during expiration in the current study was similar in magnitude to that recently reported in people with OSA and tetraplegia (Wijesuriya et al . ) to negative pressure pulses delivered during early inspiration (excitation onset both 32 ms). In addition, there were two instances of reflex inhibition before excitation during expiration in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The delayed reflex latency during expiration in the current study was similar in magnitude to that recently reported in people with OSA and tetraplegia (Wijesuriya et al . ) to negative pressure pulses delivered during early inspiration (excitation onset both 32 ms). In addition, there were two instances of reflex inhibition before excitation during expiration in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also highlight changes in genioglossus reflex responses to negative pressure pulses in people with tetraplegia and OSA, which may be an important contributor to OSA in many of these individuals (Wijesuriya et al . ). Earlier studies (Woodall et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…As a result, prevalence of obstructive sleep apnoea is greater in patients with spinal cord injury as compared to the general population (Wijesuriya et al . ). Therefore, does intermittent hypoxia provoke greater increase of frequency and duration of apnoeic/hypopnoeic events in patients with spinal cord injury than in subjects without it?…”
mentioning
confidence: 97%
“…The underlying mechanisms may also dynamically change during progression from acute to chronic SCI. A new report in this issue of The Journal of Physiology from Wijesuriya and colleagues sheds new light on this complex physiological question (Wijesuriya et al 2018). The electryomographic activity of an important pharyngeal dilator muscle -the genioglossus (GG) -was studied in two groups of individuals with OSA.…”
mentioning
confidence: 99%